PEMBINAAN INSTRUMEN PENGUKURAN SIKAP SAINTIFIK PELAJAR SEKOLAH MENENGAH RENDAH (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Scientific approach in science teaching became a major issue in science education in this country. In order for students to succeed in their scientific research, attitude and scientific skills are two important things you must have. These two important elements are rarely getattention in our science education. Thus, the researchers felt the need to find the effective ways to build both the scientific element for students. An effort in that direction is to build instruments to measure attitudes and scientific skills. In this paper, wewould like to explain the development of instruments that we have done. This instrument will be used to measure the scientific attitude of students of junior high school. Instruments were developed based on eight constructs: curiosity, respect for evidence, willingness to change ideas, critical reflection, suspended judgment, objective, rational and humility. There is a 31 item questionnaire has been declared valid through expert validation and empirical tests. The data of empirical test were analyzed using the Pearson product moment correlation. Reliability testing questionnaires of scientific attitude found Cronbach alpha coefficient of 0.677, which shows that the ability of items of the instrument measures the concepts in the study were considered satisfactory.Keywords: scientific method, scientific attitudequestionnaire, sciencelearning, validity and reliability of instruments